GAMBARAN KESEHATAN MENTAL NARAPIDANA DITINJAU DARI EMOSI PSIKIS DI POLISI RESORT PAINAN - Joni Adison; Suryadi Suryadi (Jurnal Inovasi Penelitian, 2020)
A This research is motivated by the feeling of morality that arises on the inmates involved in drug cases and theft. The presence of anxiety experienced by the inmates in the cell both psychologically and socially. But the focus in this study is: 1) The mental health deskription of the prisoners is seen from social feelings. 2) The mental health deskription of prisoners is seen from feelings of morality. This research is a qualitative descriptive research. key informants as much as 2 people and additional informants as many as 4 people, Instruments that researchers use in this research is interview. Data analysis techniques such as data reduction, data presentation, and conclusion. The results can reveal that: 1). The mental health deskription of the inmates is seen from the social feelings that prisoners are able to socialize and be able to get closer to other inmates, the inmates are able to perform activities and obey the rules that are in the cell, for example: eating together, praying congregation, sharing together and exercising together. 2). The mental health deskription of the inmates is seen from feelings of guilty that feel guilty by breaking the law and regretting his actions, the prisoners promise to serve punishment or regulation, and behave well during the sentence. Able to undergo all the obligations that are in the cell as given the responsibility for maintaining cleanliness and comfort while in the cell. Based on the results of the study can be recommended to inmates to be able to control the psychic emotions while undergoing punishment in the cell.